Peran Pekerja Sosial DKM (Dewan Kemakmuran Masjid) Masjid Al-Falah Desa Keniten di masa Pandemi Covid-19 - Aditya Wisnu Aji; Dewi Ariyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIN Prof. K.H. Saifuddin Zuhri, 2021)
This study aims to know and discuss the role of DKM (Mosque Prosperity Council) in empowering and prospering mosques. This important consideration that there is a degradation of the Muslim community phenomenon, especially in Keniten Village for praying to the mosque.To examine more deeply related to the issue, this study uses qualitative descriptive methods with phenomenological approach, therefore the researchers describe sistematicaly. The data collection technique used is observation and interviews. The results showed that the role of DKM Masjid Jami AL-Falah successfully built and increase number of mosque visitors.